URGENSI PENGATURAN ARTIFICIAL INTELLEGENCE DI INDONESIA - Mohamad Zachary Rusman; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research is an effort to respond to the times as something that cannot be stopped, one of the impacts is Artificial Intelligence technology which offers many benefits in various sectors of life. Like a double-edged sword, in addition to having a positive impact Artificial Intelligence technology also has a negative side, both of which have been clearly felt. In Indonesia there are no rules that can accommodate specifically about Artificial Intelligence both utilization and protection from its impact including. The method used in placing the point of this research problem is the normative research method. So far, Indonesia's efforts in responding to this matter have only reached the action plan, as well as the formulation of a national strategy, all of which are not sufficient to respond to the times so that the regulation of Artificial Intelligence, in this case special arrangements related to the utilization and protection of users from negative impacts, is an urgent solution.